A simple and low-cost environmental enrichment program improves the welfare of Calomys callosus, a species that adapts to animal facilities - Klein, Sandra Gabriela; Soares de Assis, Tamires; Pereira, Gabriel Silva; Coutinho, Loyane Bertagnolli; Guerra, Renan Faria; Neves, Matheus Morais; Ferreira, Flávia Batista; Lemos de Lima, Isabela; Polveiro, Richard Costa; Ferro, Eloisa Amália Vieira; Vieira da Silva, Murilo (Frontiers in Veterinary Science, 2024)
An environmental enrichment protocol is essential for testing experimental models because it upholds animal welfare, aligns with ethical principles in animal experimentation, and reduces the number of animals needed. Calomys callosus, a South American rodent from the Cricetidae family, is bred in rodent animal facilities for its ease of handling, longevity, prolificacy, and effectively mimicking diseases like Toxoplasmosis, Leishmaniasis, Chagas, and Schistosomiasis. There are no reports on environmental enrichments for this species or their impact on reproductive parameters. This study aimed to analyze the influence of the Environmental Enrichment Program (EEP) on the reproductive and zootechnical performance of C. callosus kept in the Rodents Animal Facilities Complex of Universidade Federal de Uberlândia (UFU). Two experimental groups were established: with environmental enrichment EE+ and without environmental enrichment EE−. The materials used in the experimental design were changed weekly and alternated between dietary, occupational, physical/cognitive, and non-enrichment items. After the inclusion of the EEP, an improvement in the reproductive indices of C. callosus was identified in the EE+ group. These improvements included increased female precocity, a decreased interbirth interval, and a higher number of pairs producing more offspring. The postpartum zootechnical indices were also better, such as the number of animals born alive, improved weaning rates, and a reduced average number of deaths from birth to weaning. After the inclusion of the EEP, the general health status of C. callosus improved, reducing cases of non-infectious lumbar alopecia. Therefore, EEP allows C. callosus to express natural reproductive behaviors and improves parental care.